(untitled) (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
This article aims to examine the concept of Madrasah Al-Ula as a Qur’anic interpretive construction based on the principle of wasathiyah (moderation) in the thought of M. Quraish Shihab, focusing on the synergy between domestic and public roles of Muslim women as reflected in the Qur’an. This study employs a qualitative approach through library research and thematic analysis of three major works by Quraish Shihab: Tafsir al-Misbah, Wawasan al-Qur’an, and Membumikan al-Qur’an. The findings reveal: (1) since the early period of Islam, women have played vital roles as educators and preservers of knowledge; (2) Shihab’s wasathiyah interpretation affirms gender equality in both spirituality and social responsibility; (3) women can participate in the public sphere without abandoning their maternal role; and (4) Madrasah Al-Ula emerges as a relevant model for Islamic family education in responding to contemporary challenges. This study contributes to the development of moderate gender-based Qur’anic discourse and offers an integrative model of Islamic family education responsive to the crisis of domestic values and the growing demand for Muslim women’s public engagement.